ANALISIS KEMAMPUAN LITERASI MATEMATIKA SISWA SMA MUHAMMADIYAH KUPANG DALAM MENYELESAIKAN SOAL PROGRAM LINEAR - Serang, Ifa Razia; Yusuf, St. Muthmainnah; Aba, Maria Martini (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2024)
This research aimed to analyze student literacy ability in Mathematic teaching in Muhammadiyah Senior High School (SMA Muhammadiyah) of Kupang. This research was qualitative descriptive. Subject here was student of SMA Muhammadiyah class XI MIA in Kupang. These students were categorized firstly in three ability categories i.e., high, middle, and low. Two students was taken in each category. The object here was the analysis of students’ literacy ability at SMA Muhammadiyah Kupang to solve problems in linear program. Technic in this study was purposive sampling. Data was analyzed based on test and interview results. The validity was checked using triangulation method by comparing the obtained data in interview test. Results show that the student literacy ability in mathematic was high and fulfill all indicators. Student was able to formulate mathematic model and real problems of linear program, and give implementation mathematic model design to solve mathematic solution. Student with middle literacy ability only have two indicators. These students able to make decision to problems, know some parts that needed in order to making problem model in mathematics, then make evaluation on it. Student with low literacy ability only have one indicator, which is formulate indicator. By this indicator those students able to change problem to suitable mathematic model in variable form. There for some efforts was needed in order to increase mathematic literacy to students.